Isolasi dan Identifikasi Rizobakteri dari Rizosfer Kacang Tanah dan Uji Efektivitasnya dalam Mengendalikan Penyakit Layu Fusarium pada Tanaman Tomat - SOLICHATUN, SOLICHATUN; KHALIMI, KHAMDAN; SUDARMA, I MADE (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.2, No.4, Oktober 2013, 2013)
ABSTRACT Isolation and Identification of Rhizobacteria from Peanut Rhizosphere to Control Fusarium Wilt on Tomato Tomato is one of the important horticultural in Indonesia. One obstacle in the cultivation of tomato is wilt disease caused by Fusarium oxysporum f.sp. lycopersici . Naturally soil microorganisms have the potential to suppress the development of pathogens in the soil. Population of microorganisms around rhizosphere is higher than not in rhizosphere both in quantity and quality. Legumes are known have positive effect to the microorganims in the soil due to rich N from root exudates.The purpose of this research is to determine the ability of rhizobacteria that were isolated from the rhizosphere of peanut in controlling F. oxysporum f.sp. lycopersici causes Fusarium wilt disease. Rhizobacteria as antagonist agent isolated from the rhizosphere of peanut from 3 places and tested against F. oxysporum f.sp. lycopersici in vitro and in vivo. Identification rhizobacteria with Oxoid Microbact GNB Kit.In this study, 61 isolates obtained from the rhizosphere of peanuts. However, only 4 isolates could inhibit Fusarium oxysporum f.sp. lycopersiciin vitro and only 2 isolates could identified certainly. One isolate identified as Klebsiella pneumoniae and one isolate as Stenotrophomonas maltophilia with percentage of probability above 90%. There needs to be more research on the stability of rhizobacteria in suppressing the occurance Fusarium wilt disease on tomato. Keywords: Tomato, Fusarium, and Rhizobacteria.
Keywords: Tomato, Fusarium, Rhizobacteria